2017
DOI: 10.1136/jmedgenet-2017-104922
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of telomere length among South Asians identifies a second RTEL1 association signal

Abstract: BackgroundLeucocyte telomere length (TL) is a potential biomarker of ageing and risk for age-related disease. Leucocyte TL is heritable and shows substantial differences by race/ethnicity. Recent genome-wide association studies (GWAS) report ~10 loci harbouring SNPs associated with leucocyte TL, but these studies focus primarily on populations of European ancestry.ObjectiveThis study aims to enhance our understanding of genetic determinants of TL across populations.MethodsWe performed a GWAS of TL using data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 50 publications
2
38
0
1
Order By: Relevance
“…We lack detailed monitoring to exposure data (e.g., smoking and alcohol use) for GTEx donors; studies that can link human tissue samples to environmental and lifestyle histories are needed to better understand environmental determinants of TL across different tissues and cell types. Currently, all TL-associated SNPs have been identified in genome-wide association studies of leukocyte TL (12)(13)(14)(15); our study suggests some of these effects are also present in other tissue types, but larger studies of tissue-specific TL measurements are needed to characterize how these effects vary across tissues and cell types. Identifying variants that impact TL in all or most cell types (e.g., variants with effects on TL that may be present during development or in stem cells in multiple tissue types) may be ideal for evaluating the causal impact of TL on risk for a wide array of diseases (occurring in diverse tissues or cell types) using Mendelian randomization.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We lack detailed monitoring to exposure data (e.g., smoking and alcohol use) for GTEx donors; studies that can link human tissue samples to environmental and lifestyle histories are needed to better understand environmental determinants of TL across different tissues and cell types. Currently, all TL-associated SNPs have been identified in genome-wide association studies of leukocyte TL (12)(13)(14)(15); our study suggests some of these effects are also present in other tissue types, but larger studies of tissue-specific TL measurements are needed to characterize how these effects vary across tissues and cell types. Identifying variants that impact TL in all or most cell types (e.g., variants with effects on TL that may be present during development or in stem cells in multiple tissue types) may be ideal for evaluating the causal impact of TL on risk for a wide array of diseases (occurring in diverse tissues or cell types) using Mendelian randomization.…”
Section: Discussionmentioning
confidence: 83%
“…Prior genome-wide association studies (GWAS) have identified SNPs associated with leukocyte TL (12)(13)(14)(15). We constructed a weighted polygenic SNP score for each donor using nine leukocyte TL-associated SNPs, with higher score reflecting longer TL (see Methods and Table S6) (31).…”
Section: Leukocyte Tl-associated Genetic Variants and Tl In Other Tismentioning
confidence: 99%
See 1 more Smart Citation
“…SNPs in RTEL1 are associated with glioma in large GWAS of this rare brain cancer. The glioma-associated RTEL1 SNPs are intronic, but functional studies have not yet been completed to understand their potential functions 148 152 . These findings are intriguing because patients with DC or HH due to autosomal recessive RTEL1 mutations often have abnormal brain development in the form of cerebellar hypoplasia 35 37 , 153 .…”
Section: The Advent Of Telomere Molecular Epidemiologymentioning
confidence: 99%
“…T/S ratio. Details of this methodology have been described previously 34 . Plate design 1was based on Ehrlenbach et al 35 and consisted of triplicates of 14 participant DNA samples per plate and six replicates of reference DNA sample, with telomere sequence and RPLP0 measured on the same plate.…”
Section: Measurement Of Ltl Using Qpcrmentioning
confidence: 99%